A study on the efficiency of carbon emission policy implementation in China based on a novel network super-efficiency EBM-Malmquist index - Pan, Wenchao; Lin, TsungXian; Chen, Yeying; Yuan, Liping; Lin, Qinyi; Wang, Ting (Frontiers in Environmental Science, 2026)
As the world’s largest developing country, manufacturing hub, and energy consumer, China has consistently ranked among the top global emitters of carbon dioxide. While China currently maintains a high level of control over carbon emissions, carbon emission policies remain a critical step in environmental protection. Therefore, we employ a novel network-based ultra-efficient EBM method combined with the Malmquist index to analyse panel data from 2012 to 2022, evaluating the implementation efficiency of China’s carbon emission policies over the past decade. This approach enables a more scientific quantification of their implementation efficiency and reveals the underlying mechanisms of efficiency losses, thereby promoting a transition in policy from ‘broad-based emissions reduction’ to ‘precision-based governance.’The results of the study show that: (1) the larger the size of the province, the higher the efficiency of carbon emission policy implementation. (2) In the process of regional implementation, the higher the technical efficiency and the larger the scale efficiency of the province, the higher the efficiency of carbon emission policy implementation.